KAJIAN KUALITATIF TEORI-TEORI GOOD CORPORATE GOVERNANCE DALAM TATA KELOLA PERUSAHAAN - Putri Wahyuni; Afni Haryanti Harahap; Risa Lidia Batubara; Ahmad Wahyudi Zein (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Good Corporate Governance (GCG) is a crucial aspect of Islamic banking management because Islamic banks are not only focused on financial performance but also must ensure compliance with Islamic principles. This article aims to examine theories of Good Corporate Governance and their relevance to the implementation of Islamic banking governance. The research method used is a literature review, reviewing books and journal articles related to GCG and Islamic banking. The results of the study indicate that Agency Theory, Stewardship Theory, Stakeholder Theory, Transaction Cost Theory, Political Theory, and Resource Dependency Theory complement each other in building a transparent, accountable, and equitable Islamic banking governance system. The implementation of Good Corporate Governance can increase public trust and support the sustainability of Islamic banking.